Door to relocation time for dislocated hip prosthesis: multicentre comparison of emergency department procedural sedation versus theatre-based general anaesthesia. Issue 1 (22nd December 2008) - Gagg, J; Jones, L; Shingler, G; Bothma, N; Simpkins, H; Gill, S; Benger, J; Lloyd, G
Abstract : Background: Dislocation of a hip prosthesis is a painful event which has an incidence of 4% for primary total hip arthroplasty. Relocation is traditionally performed under general anaesthesia in the operating theatre, but relocation using sedation in the emergency department (ED) has been reported, with a limited success rate of 62%. A study was undertaken to compare door to relocation times for ED sedation and theatre general anaesthesia. Methods: The notes of all patients attending five centres in the south west of England with prosthetic hip dislocation over a 12-month period between 2005 and 2006 were retrospectively reviewed using standardised data collection forms. Results: Successful ED reduction was significantly quicker than failed ED reduction and theatre-based general anaesthesia (2 h 21 min vs 8 h 32 min; p<0.001). No statistical difference was found between failed ED reduction and theatre general anaesthesia. Conclusions: Reduction of dislocated hip prostheses in the ED saves nearly 6 h compared with theatre-based general anaesthesia and is therefore advocated.